Pyroptosis-Mediated Molecular Subtypes and Tumor Microenvironment Infiltration Characterization in Colon Cancer - Rao, Jiawei; Li, Wen; Chen, Chuangqi (Frontiers in Cell and Developmental Biology, 2021)
The role of pyroptosis, which is also a kind of cell-intrinsic death mechanisms, in tumorigenesis and cancer progression has been revolutionized. However, the expression of pyroptosis-related genes (PYGs) in colon cancer and their prognosis value remains unclear. In this study, we comprehensively identified the 2 PYGs-mediated molecular subtypes (immune-activated and immune-naive) of 1415 colon cancer samples based on 10 PYGs with distinct tumor microenvironment (TME). The six-gene signature (PY-score) was constructed to quantify molecular patterns of individual tumors using LASSO-Cox regression model through differentially-expressed genes between the 2 molecular subtypes. Significantly infiltration of activated immune cells (such as M1 macrophages and cytotoxic T cells) were observed in low PY-score group, while naive and suppressive immune cells (such as naive CD8+ T cells and M2 macrophages) dominated in high PY-score group. Colon cancer patients in low PY-score group not only showed significantly survival advantage but also sensitivity to immune-checkpoint inhibitor treatment, anti-EGFR therapy and chemotherapy. This work revealed the PYGs played a vital role in formation of TME heterogeneity. The analysis for the PYGs-mediated molecular patterns helped understand the TME infiltration characterization and provide insights into more effective therapy strategies.